Grupos operativos: a construção do conhecimento mediante uma relação dialógica - Oliveira, Junio Pereira Virto de (2020)
Comprehensive education in Brazil is a recent trend, a process that is under construction requiring adaptation of the educational system, especially in its methodological aspects, thus there are great gaps in the understanding of how to operate in relation to it. Thus, it is necessary to bear in mind that the production of the curriculum of the integral school brings the challenge of placing the student as a protagonist in the learning processes. The study investigated the potential of the concepts of operative groups of Pichón-Rivièri as a methodological strategy for the development of learning in students of an integral school in the municipality of Araraquara-SP. Thus, the following research questions were defined: Can operative groups be configured as an alternative methodological strategy in a full school? How can the interrelationship between students guide the progress of a project? Is it possible for students to build learning collectively, producing new knowledge, enabling learning? As a general objective it was analyzed within the operational groups how the tasks were faced during the meetings by the students. The study was based on qualitative research, and is configured as an action research. The method used for data collection was that of participant observation, with the operative groups using mainly the recording of images and audio. Two operative groups were set up in which students were tasked with solving problematic situations culminating in the production of the online newspaper. The dialogues at the meetings produced rich material, enabling the analysis of the data through the characterization of the roles and vectors of the group process, making it possible to point out how the inter-relationship of the students provided a construction of new knowledge from a collective construction, providing opportunities learning situations.